2021
DOI: 10.1002/cld.1027
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Pediatric Nonalcoholic Fatty Liver Disease

Abstract: http://aasldpubs.onlinelibrary.wiley.com/hub/journal/10.1002/(ISSN)2046-2484/video/17-3-reading-yu a video presentation of this article http://aasldpubs.onlinelibrary.wiley.com/hub/journal/10.1002/(ISSN)2046-2484/video/17-3-interview-yu an interview with the author

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 25 publications
1
33
0
1
Order By: Relevance
“…Non-alcoholic fatty liver disease (NAFLD) is a multifaceted disease that includes a wide spectrum of liver damage, ranging from the accumulation of fat in more than 5% of hepatocytes (NAFLD) to non-alcoholic steatohepatitis (NASH), characterized by tissue necroinflammation and possible fibrosis at different stages associated with steatosis ( 1 ). NAFLD, as a feature of metabolic syndrome, is a cause of increasing concern in pediatrics, and it is estimated to affect 5–10% of children and adolescents in westernized countries ( 2 ). Several studies suggest that NASH may progress to cirrhosis and end-stage liver disease that requires liver transplantation.…”
Section: Introductionmentioning
confidence: 99%
“…Non-alcoholic fatty liver disease (NAFLD) is a multifaceted disease that includes a wide spectrum of liver damage, ranging from the accumulation of fat in more than 5% of hepatocytes (NAFLD) to non-alcoholic steatohepatitis (NASH), characterized by tissue necroinflammation and possible fibrosis at different stages associated with steatosis ( 1 ). NAFLD, as a feature of metabolic syndrome, is a cause of increasing concern in pediatrics, and it is estimated to affect 5–10% of children and adolescents in westernized countries ( 2 ). Several studies suggest that NASH may progress to cirrhosis and end-stage liver disease that requires liver transplantation.…”
Section: Introductionmentioning
confidence: 99%
“…After controlling for basic demographics and clinical risk factors for NAFLD in children (i.e., age, sex, ethnicity, BMI %, the presence of T2DM, and the presence OSA) (11)(12)(13)(14)(15), positive ANA in the setting of an ALT >80 had 4.6 greater odds of having an NAS ≥5 (P = 0.035, 95% CI, 1.12-19.01) (Table 3). After holding all other variables constant, ANCA positivity was associated with decreased odds of NAS ≥5 (odds ratio, 0.13; P = 0.022; 95% CI, 0.23-0.75) and lower PNHS % (P = 0.027; 95% CI, −39.69 to −2.51) (Tables 3 and 4).…”
Section: Resultsmentioning
confidence: 99%
“…The rate is higher in some populations such as Asians and boys. [ 17 ] The results of a recent systematic review study in Iran reported an estimated rate of 27.88% among Iranian children and adolescents. [ 18 ]…”
Section: Discussionmentioning
confidence: 99%